THE INFLUENCE OF PRODUCT QUALITY, SERVICE QUALITY, AND STORE ATMOSPHERE TOWARDS CUSTOMER REPURCHASE INTENTION AT FAT-FAT RESTAURANT IN BEKASI - Kezia Kezia; J.E. Sutanto; Moses Soediro; Adrie Oktavio (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
Research entitled